Default Sex and Single Gene Sex Determination in Dioecious Plants - Cronk, Quentin; Müller, Niels A. (Frontiers in Plant Science, 2020)
A well-established hypothesis for the evolution of dioecy involves two genes linked at a sex determining region (SDR). Recently there has been increased interest in possible single gene sex determination. Work in Populus has finally provided direct experimental evidence for single gene sex determination in plants, using CRISPR-Cas9 to knock out a single gene and convert individuals from female to male. In poplar, the feminizing factor popARR17 acts as a “master regulator”, analogous to the mammalian masculinizing factor SRY. The production of fully functional males from females by a simple single gene knockout is experimental evidence that an antagonistic male-determining factor does not exist in Populus. Mammals have a “default sex” (female), as do poplar trees (Populus), although the default sex in poplars is male. The occurrence of single gene sex determination with a default sex may be much commoner in plants than hitherto expected, especially when dioecy evolved via monoecy. The master regulator does not even need to be at the SDR (although it may be). In most poplars the feminizing factor popARR17 is not at the SDR, but instead a negative regulator of it. So far there is little information on how high-level regulators are connected to floral phenotype. A model is presented of how sex-determining genes could lead to different floral morphologies via MADS-box floral developmental genes.